Biocompatible Sensors: Biocompatible Soft Fluidic Strain and Force Sensors for Wearable Devices (Adv. Funct. Mater. 7/2019). (12th February 2019) - Xu, Siyi; Vogt, Daniel M.; Hsu, Wen‐Hao; Osborne, John; Walsh, Timothy; Foster, Jonathan R.; Sullivan, Sarah K.; Smith, Vincent C.; Rousing, Andreas W.; Goldfield, Eugene C.; Wood, Robert J.
Abstract : In article number1807058, Robert J. Wood and co‐workers describe a silicone‐based strain and force sensor composed of a novel biocompatible conductive liquid (potassium iodide and glycerol solution). This solution is not only safe to the human body, but also has higher conductivity and lower viscosity compared to previously used biocompatible liquids.